Performance of a traveling wave thermoacoustic-piezoelectric energy harvester: An electrical circuit analogy approach. (July 2014) - Roshwalb, Andrew; Nouh, Mostafa; Aldraihem, Osama; Baz, Amr
The performance of a traveling wave thermoacoustic-piezoelectric energy harvester is developed using an electrical circuit analogy approach. The harvester converts thermal energy, such as solar or waste heat energy, directly into electrical energy without the need for any moving components. The input thermal energy generates a steep temperature gradient along a porous regenerator. At a critical threshold of the temperature gradient, self-sustained acoustic waves are developed inside an acoustic resonator. The associated pressure fluctuations impinge on a piezoelectric diaphragm, placed at the end of the resonator. The resulting interaction is accompanied by a direct conversion of the acoustic energy into electrical energy. The acoustic pressure oscillations are amplified by a specially designed acoustic feedback loop that introduces appropriate phasing to make the pulsations take the form of traveling waves. Such traveling waves render the harvester to be inherently reversible and thus highly efficient. The behavior of this class of harvesters is modeled using an electrical circuit analogy approach. The developed model is a multifield model that combines the descriptions of the acoustic resonator, feedback loop, and the regenerator with the characteristics of the piezoelectric diaphragm. The onset of self-sustained oscillations of the harvester is predicted using the root locus method. The predictions are validated against published results. The developed electrical analog and the associated analysis approach present invaluable tools for the design of efficient thermoacoustic-piezoelectric energy harvesters.